Covid‐19 lockdown showed a likely beneficial effect on diabetic foot ulcers. Issue 4 (2nd February 2022) - Bonnet, Jean‐Baptiste; Macioce, Valérie; Jalek, Abdulkader; Bouchdoug, Karim; Elleau, Cécile; Gras‐Vidal, Marie‐Françoise; Pochic, Julie; Avignon, Antoine; Sultan, Ariane
Abstract: Aims: During the Covid‐19 epidemic, many countries imposed population lockdown. This study aimed to analyse diabetic foot ulcer (DFU) evolution of outpatients between the lockdown period and 1 month after its end. Materials and Methods: We conducted a prospective, observational, single‐centre study without modification of care. All patients who followed up for a DFU in the study centre between 15 April 2020 and 11 May 2020 were included. The baseline assessment occurred 4 weeks after the beginning of lockdown and the follow‐up visit 4–6 weeks after easing of lockdown. The primary analysis was based on the Site, Ischaemia, Neuropathy, Bacterial infection, Area, Depth (SINBAD) classification. Results: Twenty‐seven patients were included, median 69.4 years, and 25 were followed‐up at easing of lockdown. The median SINBAD score was 2 (interquartile range 1; 3) at inclusion and 1 (1; 2) at easing of lockdown, with a mean change of −0.32 (95% confidence interval −0.93; 0.29). Seventy‐two percent of the population had a stable or improved score between the two visits. The proportion of patients using off‐loading footwear was higher among those whose SINBAD score improved compared to those whose score worsened or remained stable (72%, 44% and 28%, respectively). Diabetes type was linked to DFU prognosis. Five patients (20%) were hospitalized during the follow‐up period. Conclusion: Lockdown appears to have had a positive effect on DFU if patients remain under the care of their expert wound centre. We believe this effect is related to better compliance with offloading. The wide use of tele‐medicine seems relevant for the follow‐up of DFU.